The Students’ Reflective Abstraction in Implementing MBKM - Risnina Wafiqoh; Fitri Apriani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2025)
Learning from the obstacles faced by other universities whose nature is administrative wise, currently questions still arise regarding the implementation of MBKM, which is about how the abilities will be developed by students who take part in the MBKM program, especially their hard skills, Reflective Abstractions. This research aims to determine the Reflective Abstractions (RA) of Students who carry out MBKM program and the factors that cause the obstacles in implementing MBKM. This research used a phenomenology method involving 6 students participating in the MBKM Mathematics Education study program. There was 1 student participating in the MBKM PMM scheme, 4 students participating in the Kampus Mengajar scheme, 1 student participating in the KKN Tematik scheme. The research results were analyzed qualitatively in four steps. This research resulted in all levels of reflective abstractions possessed by MBKM student participants. Starting from level 1, recognition; level 2, representation; level 3, structural abstraction; and level 4, structural awareness. However, not all subjects reach the level 4 of reflective abstractions and not all subjects have consistent reflective abstractions. In certain circumstances, they are facing problems that they have yet to understand from adapting MBKM activities, causing them to be unable to develop the new concepts.